2018
DOI: 10.1111/gcbb.12556
|View full text |Cite
|
Sign up to set email alerts
|

Volatile fatty acids (VFAs) and methane from food waste and cow slurry: Comparison of biogas and VFA fermentation processes

Abstract: The potential of various biomasses for the production of green chemicals is currently one of the key topics in the field of the circular economy. Volatile fatty acids (VFAs) are intermediates in the methane formation pathway of anaerobic digestion and they can be produced in similar reactors as biogas to increase the productivity of a digestion plant, as VFAs have more varying end uses compared to biogas and methane. In this study, the aim was to assess the biogas and VFA production of food waste (FW) and cow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 43 publications
5
57
2
Order By: Relevance
“…The organic waste in the study of Owusu-Agyeman et al [35] consisted of alcohol and soda beverage, food, dairy, fruit, fat, and oil waste. Tampio et al [36] reported that the acetic acid fraction dominated only in the first period of the anaerobic digestion of food waste, which was then surpassed by butyric acid. Additionally, in this case, mesophilic conditions (37 • C) [36] could be considered as a plausible explanation for the obtained difference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic waste in the study of Owusu-Agyeman et al [35] consisted of alcohol and soda beverage, food, dairy, fruit, fat, and oil waste. Tampio et al [36] reported that the acetic acid fraction dominated only in the first period of the anaerobic digestion of food waste, which was then surpassed by butyric acid. Additionally, in this case, mesophilic conditions (37 • C) [36] could be considered as a plausible explanation for the obtained difference.…”
Section: Resultsmentioning
confidence: 99%
“…Tampio et al [36] reported that the acetic acid fraction dominated only in the first period of the anaerobic digestion of food waste, which was then surpassed by butyric acid. Additionally, in this case, mesophilic conditions (37 • C) [36] could be considered as a plausible explanation for the obtained difference. The butyric and valeric acid contents were at deficient levels during AD ( Figure 4c) and did not go beyond 10 mg/kg even in the inlet section.…”
Section: Resultsmentioning
confidence: 99%
“…The contact of the activated spore with certain germinant, such as L-alanine, L-asparagine, and L-valine, induces the second stage generally regarded as germination. New growing cells are then formed in the final stage of outgrowth [146,151,152].…”
Section: Heat Shocking Of Microbial Consortiummentioning
confidence: 99%
“…The x ‐axis values of the PIs of the pretreated reactors varied between 6.64 and 7.04. At this stage of digestion, the accumulation of volatile fatty acids can have a negative effect on the bacteria . Therefore, ensuring proper pH control in the process between PAM and PI can increase the production efficiency and the curve length between these two points.…”
Section: Resultsmentioning
confidence: 99%